Personality-related and psychosocial correlates of sick leave days in Germany during the COVID-19 pandemic: findings of a representative survey - André Hajek; Hans-Helmut König (BMC, 2022)
Abstract Background The aim of our study was to assess the personality-related and psychosocial correlates of sick leave days in Germany during the COVID-19 pandemic. Methods We used data from a representative online-survey covering the general German adult population (data collection: mid-March 2022). We restricted our sample to full-time employed individuals aged 18 to 64 years (n = 1,342 individuals). Sick leave days in the preceding 12 months served as outcome measure. Validated and established tools were used to quantify personality characteristics and psychosocial factors (such as the Coronavirus Anxiety Scale or the De Jong Gierveld loneliness tool). Negative binomial regression models were used. Results After adjusting for various sociodemographic and health-related factors, regressions showed that a higher number of sick leave days was associated with lower levels of conscientiousness (IRR: 0.84, 95% CI: 0.73-0.97), higher levels of openness to experience (IRR: 1.19, 1.04-1.35), less coronavirus anxiety (IRR: 0.90, 95% CI: 0.86-0.93), and more depressive symptoms (IRR: 1.06, 1.02-1.11). Conclusion After adjusting for various sociodemographic and health-related factors, our study showed an association between personality-related and psychosocial factors with sick leave days. More research is required to clarify the underlying pathways.